Likelihood of Diabetes Mellitus Associated with Frozen Shoulder (Journal of Fatima Jinnah Medical University, 2024)
Background: Frozen Shoulder (FS), is an extremely debilitating shoulder condition that causes serious functional impairment in activities of routine work. FS causes disability in 2-3 percent of the population. In Pakistan, fewer studies have been conducted in the past describing the association between diabetes with FS. Through this study, we would like to study links, create awareness among physicians, patients and treat the underlying disease to reduce morbidity. Our study objective is to find the prevalence of diabetes in patients with FS from Islamabad and Rawalpindi.Subjects and Methods: Patients >18 years with shoulder pain or stiffness attending Shifa Medical and Pain Clinic were identified. Institutional review board and Ethical Committee approval and informed consent were obtained from the participants. A preformed questionnaire was used for the survey. The statistical analysis was carried out using the SPSS 23 version to evaluate the relationship between FS and age, sex, presence of diabetes, and control by HbA1c levels.Results: Data of 700 patients, 206(29.4%) males 494(70.6%) females with MA±SD of 54±9. 287(41%) patients were found Diabetic with FS. 228(79.4%) diabetic patients were poorly controlled having HbA1c levels of more than 7%. The patient had high HbA1c levels showing a strong correlation of uncontrolled Diabetes with FS. 39(9.4%) patients with FS were incidentally diagnosed with diabetes.Conclusion: Patients with frozen shoulder should be subjected to routine diabetes investigation and control should be monitored by blood glucose and HbA1c levels. Patients with diabetes should also be made aware of the role of glycemic control in the management of FS to prevent morbidity.
Keywords: Frozen shoulder, Diabetes Mellitus, HbA1c